Legal Awareness-Based Religiosity: Unveiling the Segmentation and Motivation of Qurbani Participants in West Sumatra - Testru Hendra; Zelfeni Wimra; Mahlil Bunaiya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
: Qurbani is perceived to be performed by people who have a lot of money, but in practice, financial capability is not the main reason why people perform qurbani. This article discusses what factors are the segmentation and motivation for performing qurbani and divides them into several reasons for qurbani participants based on age, gender, economic level, and education level. Furthermore, the segmentation of qurbani participants that has been determined is analyzed from the perspective of legal awareness, which is an indicator of the level of knowledge, understanding, attitude, and behavior. The purpose of the descriptive description of the segmentation and legal awareness of qurbani performers is to reveal the motivation of qurbani performers based on the experience of the people of West Sumatra. The method used is a mixed method (mix method), namely a qualitative-descriptive approach and a quantitative approach. The quantitative approach will measure the percentage based on the segmentation of qurbani participants, namely based on age, gender, education, and region The qualitative approach was used to analyze the qurbani participants' motivation, religious level, and legal awareness. The results showed that the segmentation of qurbani participants from the middle class is higher, as many as 42% of the total qurbani participants. The dominance of West Sumatran people's motivation for qurbani is influenced by the level of religiosity fostered through religious teachings and Ulama fatwas, while economic motivation is only one of the supporting factors, because materially, even though the community does not have economic stability, they are still enthusiastic about becoming qurbani participants with motivations based on the pattern of preparing qurbani costs and the preparation period. Furthermore, it was concluded that qurbani participants in West Sumatra have high legal awareness, this can be seen in the high level of understanding and knowledge of the qurbani law, as well as positive attitudes driven by religiosity, which strengthens social solidarity and community unity. This research implies that the participation, segmentation, and motivation of qurbani performers are not solely related to economic security, but rather to high levels of religiosity and legal awareness.